UJI EFEK ANTIPIRETIK KOMBINASI EKSTRAK ETANOL HERBA SAMBILOTO (ANDROGRAPHIS PANICULATA BURM.F. NEES.) DAN EKSTRAK ETANOL DAUN BELIMBING WULUH (AVERRHOA BILIMBI L.) PADA TIKUS PUTIH JANTAN (RATTUS NORVEGICUS) - Ibrahim, Nurhalifah; Yusriadi, Yusriadi; Ihwan, Ihwan (Univ. Tadulako, 2014)
This research is about antipyretic effect of combination ethanol extract of sambiloto (Andrographis paniculata Burm.f. Nees.) herbsand ethanol extract of belimbing wuluh (Averrhoa bilimbi L.) leaves in white male rats (Rattus norvegicus)which induced by 5 % pepton, in order to know the effect of combination and to determine the most effective dose as an antipyretic. Extract was prepared by maceration method using 70% ethanol. White rats were grouped into 7 difference treatment. Each rat was induced by using 5% peptone in dose of 250 mg/200 g Body Wight (BW). The first group was given Na CMC as a negative control. The second group was given paracetamol as a positive control. Groups of 3rd, 4th, 5th, 6th and 7th were given a combination of ethanol extract sambiloto (A. paniculata Burm.f. Nees.) herbs and ethanol extract belimbing wuluh (A. bilimbi L.) leaves in doses of (200 + 0) mg/200 g BW, (150 + 50) mg/200 g BW, (100 + 100) mg/200 g BW, (50 + 150) mg/200 g BW, and (0 + 200) mg/200 g BW, respectively. Temperature measurements of antipyretic were done for 3 hours in 30 minutes interval. Temperature data were statistically analysed using ANOVA (Analisys Of Variance) one way Anova method. The result of research was showed that combinationextract could reduce thefever. The most effective combination as an antipyretic was ethanol extract of sambiloto (A. paniculata Burm.f. Nees.) Herbs 150 mg and ethanol extract of belimbing wuluh (A. bilimbi L.) leaves 50 mg (150 + 50) mg/200 g BW. The dose has antipyretic effects that was not significant different to the positive control group(paracetamol treatment).